2013
DOI: 10.1104/pp.113.228783
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Functional Pleiotropy ofREVOLUTASubstantiated through Forward Genetics    

Abstract: In plants, genes may sustain extensive pleiotropic functional properties by individually affecting multiple, distinct traits. We discuss results from three genome-wide association studies of approximately 400 natural poplar (Populus trichocarpa) accessions phenotyped for 60 ecological/biomass, wood quality, and rust fungus resistance traits. Single-nucleotide polymorphisms (SNPs) in the poplar ortholog of the class III homeodomain-leucine zipper transcription factor gene REVOLUTA (PtREV) were significantly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…REV plays multiple and pleiotropic roles in plant development, including tissue patterning, secondary wall formation, and vascular cambium development (Robischon et al, 2011;Schuetz et al, 2013;Porth et al, 2014) and has recently been shown to play a role in modulating plant development according to light availability by interacting with light signaling pathways to mediate the shade avoidance response (Brandt et al, 2012). These findings support a role for REV in modulating plant development in response to environmental inputs.…”
Section: Rev Is a Direct Target Of Blh6 And Knat7supporting
confidence: 63%
“…REV plays multiple and pleiotropic roles in plant development, including tissue patterning, secondary wall formation, and vascular cambium development (Robischon et al, 2011;Schuetz et al, 2013;Porth et al, 2014) and has recently been shown to play a role in modulating plant development according to light availability by interacting with light signaling pathways to mediate the shade avoidance response (Brandt et al, 2012). These findings support a role for REV in modulating plant development in response to environmental inputs.…”
Section: Rev Is a Direct Target Of Blh6 And Knat7supporting
confidence: 63%
“…The repeated occurrence of ecophysiology traits associated with pleiotropic loci was notable (Table 6), particularly as these had little or no correlative relationship to biomass and/or phenology traits. Other examples of potentially pleiotropic loci have also been uncovered in P. trichocarpa (Porth et al, 2014), including a set of genes affecting phenology, wood fiber properties and disease resistance (I. Porth & J. Kl ap st e, unpublished).…”
Section: Genes With Associations Across Trait Categories and Potentiamentioning
confidence: 99%
“…involving a number of genes or gene networks), GWAS using high genome coverage of single nucleotide polymorphisms (SNP) markers has been very effective for identifying the genetic architecture underlying variability in these traits (Eckert et al ., ; Parchman et al ., ; Riedelsheimer et al ., ; Morris et al ., ; Porth et al ., ). GWAS can also uncover loci with potential pleiotropic effects that may be important to natural variation within species and their capacity for adaptation (Mackay et al ., ; Stapley et al ., ; Porth et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This TF plays an important role in laying down leaf polarity, root and vasculature [73]. REV is a part of a complex regulatory system involving auxin, transcription factors, miRNAs and carrier complex and is the key regulatory gene in plant morphogenesis [74]. Transcriptional variant of REV was regulated by miR165 and miR166 families.…”
Section: Common and Specific Mirnas And Tfs In High And Low As Genesmentioning
confidence: 99%